In the cir cle of students and like-minded people: to the 90th anniversary of L.A. Kolobaeva: review of the collective monograph “From Chekhov to Brodsky: Aesthetic and Philosophical Aspects of Russian Literature of the 20th Century”. Moscow: Publishing House of Moscow State University, 2019. 240 p. - Olga N. Chelyukanova; Alexander G. Kovalenko (RUDN Journal of Studies in Literature and Journalism, 2019)
The review touches upon the problems, which are formulated and solved by the group of authors in the scientifi c study “From Chekhov to Brodsky: Aesthetic and Philosophical Aspects of Russian Literature of the 20th Century”. The importance of scientifi c research, originality, well-based arguments of the authors position, the value and novelty of material are underlined in the review.